Belgische designers en hun interieur - Hendrikx, Diane; Verbist, Muriel (Antwerpen : Luster, 2011)
16 portraits of leading Belgian designers accompanied by photographic essays of their family homes.
volwassenen
boek
Keywords: Binnenhuiskunst; Woninginrichting